The Raunis section, central Latvia, revisited: ﬁrst luminescence results and re-evaluation of a key Baltic States stratigraphic site - Kalińska, Edyta; Alexanderson, Helena; Krievāns, Māris (Geografiska Annaler: Series A, Physical Geography, 2020)
This is an Accepted Manuscript version of the following article: Kalińska, E., Alexanderson, H. & Krievāns, M. (2020). The Raunis section, central Latvia, revisited: first luminescence results and re-evaluation of a key Baltic States stratigraphic site. Geografiska Annaler: Series A, Physical Geography, 102 (4), 376-396. It is deposited under the terms of the Creative Commons Attribution-NonCommercial License , which permits non-commercial re-use, distribution, and reproduction in any medium, provided the original work is properly cited. In interstadial deposits, sand interbeds gain limited consideration in comparison with organic sediments, and therefore tend to be underrepresented in paleoenvironmental reconstructions. The Raunis site, central-eastern Latvia, is an example where organic beds have already gained some attention and been used to understand the complex interactions between advance and retreat of the Scandinavian Ice Sheet in the region. Sandy interlayers have so far not been investigated in detail and their time of deposition has also been unknown, therefore exploring these clastic-organic sediment alternation is of interest. This study provides a new set of luminescence datings along with sedimentological information from the character of individual quartz grains as detected from scanning electron microscope analysis. Sandy interlayers are dated to between 12 and 122 ka. Fast component OSL signal dominates in all investigated samples, but several samples have broad and/or skewed dose distributions. Only one sample is considered reliable and provides an age of 12.0 ± 0.6 ka. A radiocarbon age from organic sediments in the same unit yields an age of 14 025 ± 270 cal y BP. These two dates do not agree within 2 sigma, and this is likely related to reservoir and hard water eﬀects of the radiocarbon sample. Sediments at the Raunis site fall into the Greenland Interstadial 1, but more detailed speciﬁcation is not possible. The rest of the OSL ages are older than expected, likely due to incomplete ...